Evaluation of Organoid‐Derived Exosomal microRNA as Liquid Biopsy for Colorectal Cancer: A Multicenter Cross‐Sectional Study - Atsuhiro Sasaki; Masatake Kuroha; Masaki Tosa; Seiichi Takahashi; Shinya Oomori; Eiki Nomura; Tatsuya Kikuchi; Motoyuki Onodera; Yuichiro Sato; Teruko Miyazawa; Hirofumi Chiba; Naonobu Yokoyama; et al. (Clinical and Translational Science)
ABSTRACT Exosomal microRNAs (miRNAs) are candidates for liquid biopsies. Organoid culture systems enable long‐term expansion of the colon epithelium. This study evaluated exosomal miRNAs from colorectal cancer organoids for liquid biopsy. Organoids were established from normal colon and colorectal cancer tissues. Exosomes were isolated from conditioned media. miRNAs were extracted from exosomes and compared using microarray analysis. Exosomal miRNAs expression levels in the sera of healthy patients and patients with colorectal cancer were compared at a single institution. The multicenter study was validated using miRNAs upregulated in the serum of colorectal cancer patients, along with exosomal miRNAs reported to be upregulated in colorectal adenoma organoids and sera. A total of 44 exosomal miRNAs were commonly expressed in both normal colorectal epithelial cells and colorectal cancer organoids, whereas 59 were exclusively expressed in colorectal cancer organoids. In a single‐center cohort study, two exosomal miRNAs (miR‐4284 and miR‐5100) were upregulated in the serum of colorectal cancer patients. In a multicenter study, four exosomal miRNAs (miR‐4284, miR‐5100, miR‐1246, and miR‐1290) were upregulated in the serum of patients with colorectal cancer. The combination of these four exosomal miRNAs had comparable diagnostic performance to carcinoembryonic antigen, with an area under the curve of 0.75 (95% confidence interval: 0.65–0.83) versus 0.79 (95% confidence interval: 0.70–0.87). Combining the four miRNAs with carcinoembryonic antigen improved diagnostic accuracy, with an area under the curve of 0.82 (95% confidence interval: 0.74–0.89). Exosomal miRNAs derived from colorectal cancer organoids can serve as diagnostic biomarkers for colorectal cancer.